Exploring perception of retraction based on mentioned status in post-retraction citations. Issue 3 (August 2022) - Liu, Xiaojuan; Wang, Chenlin; Chen, Dar-Zen; Huang, Mu-Hsuan
Abstract: The way retracted papers have been mentioned in post-retraction citations reflects the perception of the citing authors. The characteristics of post-retraction citations are therefore worth studying to provide insights into the prevention of the citation chain of retracted papers. In this study, full-text analysis is used to compare the distinctions of citation location and citation sentiment—attitudes and dispositions toward the cited work—between the conditions of correctly mentioning the retracted status (called CM) and not mentioning the retracted status (called NM). Statistical test is carried out to explore the effect of CM on post-retraction citations in the field of psychology. It is shown that the citation sentiment of CM is equally distributed as negative, neutral, and positive, while for NM, it is mainly distributed as the latter two. CM papers tend to cite retracted papers in Methodology, whereas NM papers cite more in Theoretical Background and Conclusion . The perception efficiency of retractions in psychology is low, where the average unaware duration (UD, the period between when the retraction note has been published and when the first citation directly pointed out its retracted status) lasts for 2.88 years. Also, UD is negatively correlated with the quantity of CM and the growth rate of NM, the proportionate change of NM before and after the first CM paper appears (P <0.01). After being aware of retractions, the average rate of change (ARC, the total change divided by its taken time) of NM declines significantly (Z=-2.823, P <0.01) whereas CM sees a raise in most disciplines, which contributes to the reduction of possible interdisciplinary impact.